Sustainability of Blood Shell (Anadara granosa) Cultivation Business in Rokan Hilir District, Riau Province - Supriadi, Supriadi; Warningsih, Trisla; Darwis, Darwis (Fakultas Perikanan dan Kelautan Universitas Riau, 2024)
This research was carried out in June-May 2023 in Rokan Hilir Regency to analyze the potential, business feasibility, and sustainability status of the Blood shell (Anadara granosa) cultivation business. The method used was a survey with a total of 10 respondents. The Fisheries and Maritime Service of Rokan Hilir Regency, Riau Province, numbered three people and seven cultivators, and purposive sampling was the technique for taking respondents. The research results show that the cultivation potential is 120,000 kg/harvest to 170,000 kg/harvest, with a Net Present Value (NPV) of 80% from IDR 65,759,767,943.09/ year. Benefit Cost Ratio (B/C Ratio) ≥1 means the business is said to be feasible and can also be continued. Internal Rate of Return (IRR) is 80%, meaning IRR > discount rate that has been determined, then the business is feasible to continue, and the interest rate used in this research is the BRI Bank interest rate of 15%, the sustainability status of the blood shell cultivation business is assessed based on five dimensions. The ecological, economic, social, technological and institutional dimensions included in the good and very sustainable categories are the environmental, economic and social dimensions, with dimension values of 82.33 to 86.96. Meanwhile, in the bad (unsustainable) and poor (less sustainable) categories, namely the technological and institutional dimensions, with dimension values of 21.54 to 34.65. Therefore, the two dimensions included in the categories of bad (unsustainable) and poor (less sustainable) concern the management and all stakeholders, who need to take corrective steps to improve the blood-shell resource in Rokan Hilir Regency.